Molecular mechanisms underlying prostaglandin E2-exacerbated inflammation and immune diseases. (29th March 2019) - Tsuge, Kyoshiro; Inazumi, Tomoaki; Shimamoto, Akira; Sugimoto, Yukihiko
Abstract: Prostaglandins (PGs) are the major lipid mediators in animals and which are biosynthesized from arachidonic acid by the cyclooxygenases (COX-1 or COX-2) as the rate-limiting enzymes. Prostaglandin E2 (PGE2 ), which is the most abundantly detected PG in various tissues, exerts versatile physiological and pathological actions via four receptor subtypes (EP1–4). Non-steroidal anti-inflammatory drugs, such as aspirin and indomethacin, exert potent anti-inflammatory actions by the inhibition of COX activity and the resulting suppression of PG production. Therefore, PGE2 has been shown to exacerbate several inflammatory responses and immune diseases. Recently, studies using mice deficient in each PG receptor subtype have clarified the detailed mechanisms underlying PGE2 -associated inflammation and autoimmune diseases involving each EP receptor. Here, we review the recent advances in our understanding of the roles of PGE2 receptors in the progression of acute and chronic inflammation and autoimmune diseases. PGE2 induces acute inflammation through mast cell activation via the EP3 receptor. PGE2 also induces chronic inflammation and various autoimmune diseases through T helper 1 (Th 1)-cell differentiation, Th 17-cell proliferation and IL-22 production from Th 22 cells via the EP2 and EP4 receptors. The possibility of EP receptor-targeted drug development for the treatment of immune diseases is also discussed.